Staff and voice hearer perspectives on Hearing Voices Groups in the NHS: a mixed-methods cross-sectional survey - Branitsky, Alison; Morrison, Anthony P.; Longden, Eleanor; Bucci, Sandra; Varese, Filippo (Frontiers in Psychology, 2025)
IntroductionFor over 40 years, Hearing Voices Groups (HVGs) have provided a space for individuals distressed by hearing voices to share their experiences openly. Most of these groups have existed in the community and adhere to a unique ethos which, at times, may be antithetical to that of mental health services. Recently, HVGs have started to be run within statutory services, including the UK’s National Health Service (NHS), raising questions about the practical and ideological barriers and facilitators to their successful implementation.MethodsNHS staff (N = 49) and HVG members (N = 26) took part in a mixed-methods survey aimed at understanding their perspectives on delivering HVGs in the NHS.ResultsOverall, both staff and HVG members expressed enthusiasm for HVGs in the NHS, recognising their role in fostering peer connection, though staff raised concerns about risk management and HVG members questioned whether NHS-run groups could fully uphold HVG ethos.DiscussionWhilst HVGs offer a promising user-led approach, further research is needed to understand precisely how to run these types of groups in statutory services.